Rich-phosphorus/nitrogen co-doped carbon for boosting the kinetics of potassium-ion hybrid capacitors. Issue 1 (29th November 2021) - Xie, Zhenyu; Xia, Jiannian; Qiu, Daping; Wei, Jinying; Li, Min; Wang, Feng; Yang, Ru
Abstract : An advanced potassium-ion hybrid capacitor with excellent energy density, awesome power density, and superior cycle lifespan is constructed by a phosphorus and nitrogen co-doped carbon-material anode and a hierarchical porous carbon cathode. Abstract : Potassium-ion hybrid capacitors (PIHCs) meeting the high power density of capacitors and high energy density of batteries are seen as one of the most promising energy storage devices. However, this wonderful scene is undermined by the sluggish kinetics in the anode of PIHCs. Herein, a phosphorus and nitrogen co-doped carbon material (PNC) with a wide layer spacing (0.381 nm) and high content of phosphorus (1.27 at%) and nitrogen (6.37 at%) was synthesized with non-toxic pyrrole and phytic acid as the precursors by polymerization and carbonization. The wide layer spacing and rich heteroatoms served to accelerate the diffusion rate of potassium ions and increased the adsorption capacity of potassium ions. Benefiting from these characteristics, PNC delivered a remarkable specific capacity of 310 mA h g −1 at 0.025 A g −1, and a splendid rate capability of 149 mA h g −1 at 5 A g −1 . As expected, the dual-carbon PIHC consisting of a PNC anode and a hierarchical porous carbon cathode delivered excellent energy density (103 W h kg −1 ), extraordinary power density (6106.2 W kg −1 ), and superior cycle lifespan. Our method can effectively solve the problems of the slow kinetics and low capacity of PIHCs, and provide a reference for further stimulation of their potential.